Potret Sistem Pendidikan India Era Kontemporer: Tetap Solid Pada Kebijakan Ghandi - Ali Sobri; Komarudin Sassi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The education system in India itself is very advanced, where the first university in the world was in India with 1000 lecturers in the 6th and 7th centuries, and India itself has a library that is open 24 hours a day, which is very different for Indonesia. So you can study or read anytime in the library. For the learning process, there are also many classes outside the natural class. In fact, Islamic education in India, such as Madrasahs, developed by collaborating the Madrasah curriculum with the modern curriculum, so that many students study there. It is recorded that Muslim students do not study, but the majority of Hindu students study in madrasas. Even though it is called a madrasa, the local community considers it a good public school. Like the Orgram Madrasa, which is 125 km north of the state capital, Kolkata says its modern curriculum has made the institution increasingly popular among the majority Hindu community. “Most people think madrasas are places where students are only taught religion and have nothing to do with modern education. Teachers there say they have worked for years to change their minds. In India it is different from in Indonesia when children come out. .school / study at school .In India, the teacher does not go home immediately when the teacher comes home. However, the student's parents invite the teacher to stay/visit the student's parents. Providing additional lessons at students' homes. Teachers' families are well served by teachers who receive lessons by calling the teacher's home for additional lessons.